The notarial inventory and the auction report as intertextual acts - Kuć, Joanna (Papers in Linguistics, 2024)
This article presents the phenomenon of intertextuality in the 19-century inventory deeds and auction reports from the notary’s office of Piotr Żaboklicki from Węgrów, officiating at the castle in Liw. In both types of acts we find many signals of reciprocal textual relations, which assume the form of structural references and interactions of pragmatic, stylistic, genre and communicative nature. The article identifies and describes them, also presenting the conditions and functions of these intertextual references.